Scaffolding Discovery Learning Spaces - Hai-Jew, Shalin (My University, 2010)
Discovery learning spaces may be created in online learning environments to encourage learner-directed training and learning. Such “autodidaxy” learning tends to be autonomous and learner-directed. This chapter addresses the importance of learner empowerment through the building of learner orientation, decision supports, community supports, and new learning archival. This also advocates promotion of learner selfefficacy and decision-making. The Web-based design of online discovery spaces needs to be aligned in pro-learning ways based on relevant theory, research and in-field applied practices.
Keywords: Autodidaxy; Discovery learning; Independent learning; Motivational interference; Self-directed learning; Self-regulated learning; Self-efficacy